DIDACTIC FEATURES OF PEDAGOGICAL TECHNOLOGIES IN THE TRAINING OF PRIMARY SCHOOL TEACHERS - Prots, Marta (Mountain School of Ukrainian Carpaty, 2021)
The article identifies theoretical aspects of educational technologies and their significance in the organization of the educational process in general secondary education and higher education. The potential and objectives of applying educational technologies in the training of future primary school teachers in the environment of innovation and reform of the New Ukrainian School are outlined. The efficiency of the interaction between the educational process participants in "teacherstudent" and "student-student" positions is substantiated. Specific aspects of the application of interactive pedagogical technologies that facilitate an atmosphere of cooperation, interaction, co-learning, mutual learning, are identified. The requirements for the teacher’s professionalism in interactive learning (vivid personal qualities, humanistic approach, willingness to cooperate with students and their parents, as well as within the educational environment, etc.) are outlined. The willingness to cooperate is highlighted as the main indicator of a teacher’s professional level. The organization of interactive learning is described, which involves the use of role-playing games, discussion-based learning, situational modeling, collaborative problem solving, according to the relevant circumstances and situation. The role and significance, tasks of developmental learning technology are set out. In particular, among the tasks important in the professional training of primary school teachers, the tasks of developmental learning include the ability to think independently, argue, defend one’s opinions, ask questions, be proactive in acquiring new knowledge, think critically. In preparation for the lesson, the teacher purposefully selects such tools that will contribute to the intensive formation of students' personalities. Features of design technology are revealed: specifics, classifications and features of the organization. Pedagogical technologies can be mobile, which makes them extremely effective in the process of pedagogical and specialized training of future primary school teachers.